Agreement and differentiation of intradural spinal cord lesions in dogs using magnetic resonance imaging. (3rd December 2021) - Krasnow, Maya S.; Griffin, John F.; Levine, Jonathan M.; Mai, Wilfried; Pancotto, Theresa E.; Kent, Marc; Harcourt‐Brown, Thomas R.; Carrera‐Justiz, Sheila C.; Gilmour, Lindsey J.; Masciarelli, Amanda E.; Jeffery, Nicholas D.
Abstract: Background: Magnetic resonance imaging is the method of choice for diagnosing spinal cord neoplasia, but the accuracy of designating the relationship of a neoplasm to the meninges and agreement among observers is unknown. Objectives: To determine agreement among observers and accuracy of diagnosis compared with histology when diagnosing lesion location based on relationship to the meninges. Animals: Magnetic resonance images from 53 dogs with intradural extramedullary and intramedullary spinal neoplasms and 17 dogs with degenerative myelopathy. Methods: Six observers were supplied with 2 sets of 35 images at different time points and asked to designate lesion location. Agreement in each set was analyzed using kappa ( κ ) statistics. We tabulated total correct allocations and calculated sensitivity, specificity, and likelihood ratios for location designation from images compared with known histologic location for lesions confined to 1 location only. Results: Agreement in the first set of images was moderate ( κ = 0.51; 95% confidence interval [CI], 0.43‐0.58) and in the second, substantial ( κ = 0.69; 95% CI, 0.66‐0.79). In the accuracy study, 180 (75%) of the 240 diagnostic calls were correct. Sensitivity and specificity were moderate to high for all compartments, except poor sensitivity was found for intradural extramedullary lesions. Positive likelihood ratios were high for intradural extramedullary lesions and degenerative myelopathy. Conclusions and Clinical Importance: Overall accuracy in diagnosis was reasonable, and positive diagnostic calls for intradural extramedullary lesions and negative calls for intramedullary lesions are likely to be helpful. Observers exhibited considerable disagreement in designation of lesions relationship to the meninges.